Integral Logistics Management: Planning and Control of Comprehensive Supply Chains, Second Edition - Schoensleben, Paul (CRC Press, 2009)
* Follows complete flow of material and data control through the product life cycle * Discusses the management of business processes, competent engineering, and the sensible use of activity-based costing * Includes process flow oriented concepts for the process industry * Presents a new method of mixed manufacturing and a thorough discussion of computer support through logistics software